The impact of making music on aural perception and language skills: A research synthesis (UCL Press, 2017)
This paper provides a synthesis of research on the relationship between music and language, drawing on evidence from neuroscience, psychology, sociology and education. It sets out why it has become necessary to justify the role of music in the school curriculum and summarizes the different methodologies adopted by researchers in the field. It considers research exploring the way that music and language are processed, including differences and commonalities; addresses the relative importance of genetics versus length of time committed to, and spent, making music; discusses theories of modularity and sensitive periods; sets out the OPERA hypothesis; critically evaluates research comparing musicians with non-musicians; and presents detailed accounts of intervention studies with children and those from deprived backgrounds, taking account of the importance of the nature of the musical training. It concludes that making music has a major impact on the development of language skills.